2022
DOI: 10.1590/s1677-5538.ibju.2021.0645
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D deficiency in children with overactive bladder related urinary incontinence

Abstract: Purpose: Overactive bladder (OAB) is a common syndrome associated with lower urinary tract symptoms (LUTS), especially urinary incontinence in children, which may affect the patient's quality of life (QoL). Vitamin D deficiency has been shown to be associated with OAB syndrome. This study evaluated the relationship between vitamin D status and OAB-related symptoms and QoL in children. Materials and Methods:The study included 52 pediatric patients with OAB-related urinary incontinence and 41 healthy children. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…12 Similar to previous findings in children, our results also suggested that the subset with lower vitamin D levels (below 20 ng/mL) demonstrated an augmented voiding frequency at the initial visit and a heightened effectiveness compared to the cohort possessing higher vitamin D levels (20-35 ng/mL) after VDS intervention. 14 No discernible difference emerged in the primary outcomes between the “never group” and the “ever group,” stratified by their VDS history, nor between the “worse response group” and the “better response group,” categorized by whether vitamin D levels surpassed 10 ng/mL following supplementation. Recognizing the constraints of post-hoc analyses and potential disparities in baseline, these findings warrant careful interpretation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 Similar to previous findings in children, our results also suggested that the subset with lower vitamin D levels (below 20 ng/mL) demonstrated an augmented voiding frequency at the initial visit and a heightened effectiveness compared to the cohort possessing higher vitamin D levels (20-35 ng/mL) after VDS intervention. 14 No discernible difference emerged in the primary outcomes between the “never group” and the “ever group,” stratified by their VDS history, nor between the “worse response group” and the “better response group,” categorized by whether vitamin D levels surpassed 10 ng/mL following supplementation. Recognizing the constraints of post-hoc analyses and potential disparities in baseline, these findings warrant careful interpretation.…”
Section: Discussionmentioning
confidence: 95%
“…13 Moreover, a recent trial showed a treatment benefit of high-dose VDS in reducing OAB-related incontinence in children with vitamin D deficiency. 14 However, whether high-dose VDS is effective and safe in mitigating OAB-dry symptoms in children with lower vitamin D levels remain unknown.…”
mentioning
confidence: 99%
“…A study found that vitamin D supple-mentation could decrease the frequency of bedwetting in children (23). Another study showed that vitamin D deficiency was more prevalent in overactive bladder children, and that vitamin D intake may improve LUTS (24). In another study, however, vitamin D supplementation was not recommended for this purpose (25).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Özçift and colleagues from Turkey presented in page 316 (8) a nice sudy about the relationship between vitamin D status and Overactive bladder (OAB)-related symptoms and quality of life (QoL) in children and concluded that Vitamin D deficiency is more common in children with urinary incontinence and OAB than in healthy children. Although vitamin D deficiency is not routinely evaluated for every patient, it should be evaluated in treatment-resistant OAB cases.…”
mentioning
confidence: 99%